Netcare Breast Care Centre of Excellence : what opportunity in African medical tourism? - Beswick, Claire; Ahwireng-Obeng, Fred ([London] : SAGE, 2016)
In August 2006, Dr Richard Friedland, the chief executive officer of Netcare Holdings, which operated the largest private hospital network in South Africa, was looking at the findings of research into the opportunity that medical tourists from Africa presented for the group's Breast Care Centre of Excellence. Traditional thought was that because poverty was so widespread in Africa, the possibility of attracting medical tourists from Africa to South Africa was minimal. Reading the report, Friedland now wondered whether this was indeed the case - and, if not, how the centre could exploit the opportunity such tourism presented.
Originally Published in: Beswick, C., & Ahwireng-Obeng, F. (2013). Netcare Breast Care Centre of Excellence: What Opportunity in African Medical Tourism? WBS-2013-17. Johannesburg: The Case Centre, Wits Business School.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; Netcare Breast Care Centre of Excellence; Medical tourism -- Africa -- Case studies; Breast -- Cancer -- Patients -- Care -- Africa -- Case studies; Welfare economics -- Case studies